2017
DOI: 10.1104/pp.16.01815
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Freezing Dynamics in Trees: A Simple Phase Shift Causes Complexity

Abstract: (S.M.).During winter, trees have to cope with harsh conditions, including extreme freeze-thaw stress. This study focused on ice nucleation and propagation, related water shifts and xylem cavitation, as well as cell damage and was based on in situ monitoring of xylem (thermocouples) and surface temperatures (infrared imaging), ultrasonic emissions, and dendrometer analysis. Field experiments during late winter on Picea abies growing at the alpine timberline revealed three distinct freezing patterns: (1) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 68 publications
3
53
0
2
Order By: Relevance
“…In each of these cases, the critical C again depends on g. Cochard et al (2009) demonstrated that low g, experimentally reduced by artificial surfactants, increases the vulnerability to xylem embolism in conifers, which supports the hypothesized air-seeding mechanisms (rather than mechanical failure; Delzon et al, 2010). Also, freeze-thaw-induced xylem embolism probably is based on an air seeding-like process during freezing (Charrier et al, 2014(Charrier et al, , 2017Mayr and Ameglio, 2016) and the expansion of bubbles on thawing when tensions in the xylem sap overcome g (bubble expansion hypothesis; Davis et al, 1999;Sperry, 2003, 2006;Mayr and Sperry, 2010). As air is not soluble in ice, gas bubbles form in the conduits while freezing, and, upon thawing, when the pressure of the surrounding xylem sap is sufficiently negative to counter the bubblecollapsing force of g, they will expand rather than dissolve (Pittermann and Sperry, 2006;Mayr and Sperry, 2010).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In each of these cases, the critical C again depends on g. Cochard et al (2009) demonstrated that low g, experimentally reduced by artificial surfactants, increases the vulnerability to xylem embolism in conifers, which supports the hypothesized air-seeding mechanisms (rather than mechanical failure; Delzon et al, 2010). Also, freeze-thaw-induced xylem embolism probably is based on an air seeding-like process during freezing (Charrier et al, 2014(Charrier et al, , 2017Mayr and Ameglio, 2016) and the expansion of bubbles on thawing when tensions in the xylem sap overcome g (bubble expansion hypothesis; Davis et al, 1999;Sperry, 2003, 2006;Mayr and Sperry, 2010). As air is not soluble in ice, gas bubbles form in the conduits while freezing, and, upon thawing, when the pressure of the surrounding xylem sap is sufficiently negative to counter the bubblecollapsing force of g, they will expand rather than dissolve (Pittermann and Sperry, 2006;Mayr and Sperry, 2010).…”
mentioning
confidence: 77%
“…As shown in Figure 1, it instead reached up to 70% to 80% in both species. One reason for this unexpected high embolism is the combination of freezethaw events (Mayr et al, 2003a;Pittermann and Sperry 2006) and frost drought at the timberline, but shifts in the in situ vulnerability now appear to be a second important aspect: as g plays a crucial role defining the stability of bubbles and air-water menisci during frost drought, freezing, and thawing (see introduction; Mayr and Sperry, 2010;Charrier et al, 2014Charrier et al, , 2017Mayr and Ameglio, 2016), low g increases the risk of xylem embolism during winter while it decreases it during spring. One might also speculate that the observed changes during spring play a role in refilling processes reported in a previous study .…”
mentioning
confidence: 99%
“…This is only true for nanometer-sized droplets because the freezing temperature is dependent on droplet volume and cooling rate, and the classical nucleation theory predicts a homogeneous freezing temperature of about 240 K (−33 • C) for microliter-volume droplets using a cooling rate of 1 K min −1 (Fornea et al, 2009;Murray et al, 2010;Pruppacher and Klett, 1997;Tobo, 2016). However, several studies reported average freezing temperatures for microliter-volume droplets of pure water at significantly higher temperatures because of possible artifacts (e.g., Conen et al, 2011;Fröhlich-Nowoisky et al, 2015;Hill et al, 2016;Whale et al, 2015). To our knowledge, only two studies reported an average homogeneous freezing temperature of 240 K (−33 • C) for microliter-volume droplets and a cooling rate of 1 K min −1 , using hydrophobic surfaces as a contact area for the droplets (Fornea et al, 2009;Tobo, 2016).…”
Section: Pure Watermentioning
confidence: 99%
“…Wisniewski et al (1997) evaluated the IR video thermography under controlled conditions and determined it as an excellent method for directly observing ice nucleation and propagation in plants. Since then, IR video thermography has been used in a range of studies investigating freezing in plants (e.g., Ball et al, 2002;Carter et al, 1999;Charrier et al, 2017;Fuller and Wisniewski, 1998;Hacker and Neuner, 2007;Pearce and Fuller, 2001;Sekozawa et al, 2004;Stier et al, 2003;Wisniewski et al, 2008;Workmaster, 1999). Further applications of IR video thermography are investigations of cold thermal stress in insects (Gallego et al, 2016), monitoring of freeze-drying processes (Emteborg et al, 2014), as well as detection of ice in wind turbine blades (Gómez Muñoz et al, 2016) and helicopter rotor blades (Hansman and Dershowitz, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Embolisms are a critical determinant of plant success as they can lead to loss of hydraulic, and therefore photosynthetic, function; when ‘runaway’ emboli spread between adjacent files of conduits, plant death may even occur (Tyree & Sperry, ; Tyree & Ewers, ; Cochard et al ., ). While we lack a complete understanding of embolism risk (Charrier et al ., ), evidence suggests 0.044 mm conduit diameter (or 0.0015 mm 2 cross‐sectional area, assuming circular conduits) forms a boundary above which conduits are more prone to freezing‐induced embolisms at modest water tensions (Davis et al ., ): larger conduits allow more air bubbles to coalesce, increasing the risk that they fill the conduit, causing an embolism. To avoid freezing, some lineages of woody evergreen species may have evolved an herbaceous habit (Judd et al ., ; Zanne et al ., ).…”
Section: Introductionmentioning
confidence: 99%